How forage form can affect the fatty acid composition of animal products in the autumn-lambing flock - Joy M.; Sanz A.; Ripoll-Bosch R.; Estopañán G.; Ripoll G.; Blasco I.; Álvarez-Rodríguez J. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
The study was carried out to evaluate the effect of forage form around parturition on fatty acid (FA) composition of ewes' milk and on meat from suckling lambs (10-12 kg BW). Forty eight Churra Tensina ewes rearing single lambs were assigned to one of four treatments in a 2 x 2 factorial design. The factors were the physiological status (pre-partum, last month of pregnancy, vs post-partum, 5 weeks of lactation) and the feeding system (grazing vs hay indoors). From lambing to the target BW of lambs, weekly milk samples were recorded. After slaughter, samples of M. Longissimus dorsi muscle were taken. Both products were used to determine FA content. Results show that forage form around parturition affects milk FA of ewes, the post-partum period exerting greater influence than the pre-partum period. Forage source influences the intramuscular FA composition of suckling lambs meat to a lesser extent. CLA and n6/n3 ratio are the most affected by grazing, with a positive effect of this feeding management for human health. Prepartum grazing, regardless of post-partum feeding, can improve the FA composition, increasing the CLA content in both milk and meat.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)